Women's Authorship and the Early Gothic : Legacies and Innovations. - Hudson, Kathleen (Gothic literary studies., 2020)
This collection examines Gothic fiction written by female authors in the late eighteenth and early nineteenth centuries. Analysing works by lesser known authors within a historical context, the collection offers a fresh perspective on women writers and their contributions to Gothic literature.